English language requirements for enrolment in EMI programs in higher education: A European case. Issue 47 (September 2020) - Dimova, Slobodanka
Abstract: While many studies investigate the validity of TOEFL and IELTS scores, as well as stakeholders' opinions about their usefulness for international student admission at Anglophone universities, little is known about their utility and relevance for admission in English medium instruction (EMI) programs at non-Anglophone universities. The purpose of this study is to explore various political, economic, socio-cultural, and academic dimensions within a specific EMI context in order to build an argument regarding the usefulness of standardized English test score requirements by detailing the consequences that would result from the use of standardized test scores and the decisions based on their use within the EMI context. Data from a lecturer survey, interviews, and documents were used for the analysis. Based on the findings, the use of commercial English test scores will streamline the screening of all students based on English language proficiency and establish equality among different student groups. However, although these scores may provide a solution to some language-related issues in content learning in EMI, broader educational planning (e.g., secondary school education, teacher training, integrating content and language) may be necessary in order to achieve long-term positive effects and avoid political and ethical issues. Highlights: Analysis of contextual dimensions in evaluation of standardized EAP test score utility. Contextual dimensions affect choice and use of EAP test scores for university entry. European EMI university contexts differ from those at Anglophone universities.